2017
DOI: 10.1002/star.201600247
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and structural changes of starch during processing by melt blending

Abstract: The morphological and structural changes of the granule architecture of normal starch during the melt blending in a batch mixer were investigated. Native potato, maize, and chestnut starch with different crystal structures were used as raw materials. Samples obtained at different times of melt blending were characterized by X‐ray diffraction (XRD), scanning electron microscopy (SEM), and polarized light (PL) microscopy techniques. The variation of torque versus time depended on the starch type; the thermo‐plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…However, for blends with acids, less quantity of energy was consumed and the starch maintained its granule structure. These results corroborated the literature data, where is possible perceive that a higher torque is required for destruction/melting of starch particles [4]. Also, as already discussed, acids act also as aid processing agent, lowing the shear stresses, which might be not enough to destroy the starch granules.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…However, for blends with acids, less quantity of energy was consumed and the starch maintained its granule structure. These results corroborated the literature data, where is possible perceive that a higher torque is required for destruction/melting of starch particles [4]. Also, as already discussed, acids act also as aid processing agent, lowing the shear stresses, which might be not enough to destroy the starch granules.…”
Section: Resultssupporting
confidence: 91%
“…This behavior was attributed to the higher phosphorus content on potato starch [39,58]. Castaño et al [4] demonstrated that phosphorus content influences starch plasticization in shear, where the repulsion between phosphate groups facilities the diffusion of plasticizer into starch chains, changing starch-paste viscosity. Probably, this effect also explains the higher elongation at break values for potato blends with C18 (Table 1) rather than C14, once stearic acid (C18) has higher molar mass.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The repulsion between phosphate groups made it easier to disrupt the amylopectin‐amylopectin hydrogen bonds in the double helices and destroy the crystalline of starch. Therefore, the ordered structure of starch granules with low phosphorus content was less disrupted . Starch‐bound phosphate played an important role in determining the starch viscosity characteristics.…”
Section: Resultsmentioning
confidence: 99%